Canoe slalom C1 stroke technique during international competitions - Tilden, M. L.; Oberoi, A. R.; Wakeling, J. M. (Sports Biomechanics, 2021)
The purpose of this study was to compare the frequency and duration of on-side and off-side strokes and stroke transitions between male and female canoe slalom athletes during international competitions. We analysed 33 International Canoe Federation World Cup, World Championship and European Canoe Association Championship canoe slalom race videos, from 2018 to 2020, frame-by-frame. We recorded drive durations and transition durations for each race run. We also recorded the frequency of different stroke types and transition types used in each run. Stroke timing parameters differed between female and male athletes. We found that female athletes performed a significantly greater proportion of switch transitions and on-side strokes. Male athletes performed a significantly greater proportion of cross transitions and off-side strokes. Male athletes performed significantly faster cross transitions. On-on and off-off transition durations were significantly faster than cross transitions, and cross transitions were significantly faster than switch transitions. Females had a significantly longer drive duration and lower stroke frequency compared to males. Overall, stroke and drive durations of on-side strokes and off-side strokes were not significantly different. This study identifies stroke technique differences between male and female canoe slalom athletes which can be used as a basis for future research and training.